2004
DOI: 10.1111/j.1365-2788.2005.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of social support and hardiness with mental health among mothers of adult children with intellectual disability

Abstract: The findings suggest that strengthening personal and social resources of mothers of adult children with developmental disabilities may be beneficial for their mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…The stress experienced by family caregivers who raise children with ID is affected by many factors such as the child's conditions (levels of disability and of maladaptive behaviour) and available family resources or social support (Abbeduto et al, 2004;Baker et al, 2003;Beck, Hastings, & Daley, 2004;Ben-Zur, Duvdevany, & Lury, 2005;Hodapp, Ricci, Ly, & Fidler, 2003). However, there are few initiatives in place that focus on stress-relief programs to improve the quality of life of the caregivers of people with ID.…”
Section: Introductionmentioning
confidence: 96%
“…The stress experienced by family caregivers who raise children with ID is affected by many factors such as the child's conditions (levels of disability and of maladaptive behaviour) and available family resources or social support (Abbeduto et al, 2004;Baker et al, 2003;Beck, Hastings, & Daley, 2004;Ben-Zur, Duvdevany, & Lury, 2005;Hodapp, Ricci, Ly, & Fidler, 2003). However, there are few initiatives in place that focus on stress-relief programs to improve the quality of life of the caregivers of people with ID.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, Saloviita et al (2003) showed that the most important predictor of parental stress is a negative definition of the situation. However, other studies have measured positive aspects that protect the family from stress and reduce the impact of the disability, such as: a) hardiness (Ben-Zur et al, 2005;Gill & Harris, 1991;Weiss, 2002); b) self-efficacy (Hastings & Brown, 2002); c) ambiguous loss (Boss, 1988(Boss, , 1999; and d) sense of coherence (Olsson & Hwang, 2002). The sense of coherence (SOC) has been shown to be a protective factor in stress research in studies focused on family resilience across different contexts and disorders (McCubbin et al, 1998).…”
Section: Perception Of the Problemmentioning
confidence: 99%
“…Hatton and colleagues (2010) have implicated the role of human and social capital in mediating the effects of behavioral problems. Similarly, Ben-Zur, Duvdevany, and Lury (2005) found that social support was negatively correlated with maternal stress. Research has implicated various personal and situational characteristics of the caregiver in mediating caregiver stress.…”
Section: Discussionmentioning
confidence: 93%